Antioxidant and Antibacterial Activity of Various Fractions of Heterotrigona itama Propolis Found in Kutai Kartanegara - Kustiawan, Paula Mariana; Aziz, Abdul; Yuliawan, Veggy Nadia (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: In the current pandemic era, people are trying to find additional income, such as stingless bee cultivation. Especially bee species of Heterotrigona itama, because the selling value of stingless bee honey for maintaining health is quite high. However, the potential of other bee products such as propolis is still underutilized. AIM: In this study, the antioxidant and antibacterial activity of propolis from various fractions were investigated. MATERIALS AND METHODS: H. itama propolis was extracted with 96% ethanol to obtain ethanol extract propolis (EEP). Then, it was used for liquid-liquid partition with different polarities (n-hexane and ethyl acetate) to obtain the n-hexane fraction (HF) and ethyl acetate fraction (EAF). These fractions were tested for antioxidants using the DPPH method and antibacterial against bacteria Propionibacterium acne, Staphylococcus aureus, and Escherichia coli using the agar well diffusion method. Vitamin C was used as a positive control in the antioxidant assay and Thiampenicol was used in the bacterial assay. RESULTS: The EAF had better antioxidant activity (IC50 128.46 ug/mL) than the ethanol extract (IC50 205.86 ug/mL) and n-HF (IC50 350.01 g/mL). Antibacterial activity of EEP at 200 ug/mL against P. acne was 6 ± 1.5 mm, which was categorized as medium inhibition, while the other fractions were classified as weak. CONCLUSION: EAF had the highest antioxidant activity, meanwhile EEP is the most potent on antibacterial activity. The results obtained are influenced by the environment, where the sample is taken, which is less varied in plant sources and the time of sample collection.